Seismic site classification of Nakhon Nayok City, central Thailand, using the MASW technique - Thitimakorn, Thanop; Arjwech, Rungroj; Kupongsak, Sasikan (Frontiers in Earth Science, 2023)
Shear-wave velocity (Vs) of soils in Nakhon Nayok City (NNC), Central Thailand were determined using the Multi-Channel Analysis of Surface Wave technique. The Vs of 35 tested sites were weighted average to 30 meters depth based on the National Earthquake Hazards Reduction Program (NEHRP) criteria, which revealed NEHRP site classes C, D, and E within the study area. Soil class C was found in the north of the city. Moreover, most of the residential area of NNC is positioned on soil classes D and E. Soil in the area of study has an amplification value ranging from 1.4 to 3.9. The central and southwestern parts of the city, which consist mostly of soft sediments, have a higher amplification value than that in the northern part, which mostly consists of coarse grain soils of colluvial deposits. Based on the NEHRP and amplification value, the NNC area will experience some effect from ground shaking from nearby and far away earthquake seismic sources.